Manajemen Jejaring Kerjasama Pondok Pesantren - Prayoga, Ari; Jahari, Jaja (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2019)
This paper aims to uncover the management study of the pesantren cooperation network which discusses: (1) the pattern of internal cooperation between pesantren, and (2) the pattern of external cooperation of pesantren in pondok pesantren Al-Istiqomah. This study uses a qualitative method with a case study based on intrinsic design. Data collection was carried out using interviews, documentation, and participatory observation. The data that has been collected is tested for its truth, compatibility, and compatibility through the triangulation method and other sources. Then the data is compiled, analyzed, and integrated in each case study case, and compared with other data. Then conclusions can be drawn from the findings of this study that the Collaborative Management implemented at pondok pesantren Al-Istiqomah always cooperates with the government, donors and the community because it prioritizes in the field of education with the aim of assisting the development of school building infrastructure, maintenance and care of pondok pesantren. This was done so that the pondok pesantren Al-Istiqomah could develop and could support the learning facilities of the students.